Translation Techniques, Methods, and Ideologies of Tiara Andini and Arsy Widianto’s Song Lyrics ‘Cintanya Aku’ by Emma Hesteers - Mukminin, Muhamad Saiful (JULIET: Journal of English Language and Literature, 2024)
The present research aims to examine the techniques, methods, and ideologies of translating the lyrics of the song Cintanya Aku from Indonesian into English. The song is originally sung by Tiara Andini and Arsy Widianto, and covered in English by Emma Hesteers. The present research employs a descriptive qualitative research approach with a focus on translation outcomes as the product. Data is gathered from the lyrics of Cintanya Aku in both Indonesian and English versions. Data collection involves recording and note-taking techniques, where the songs are transcribed into written form. Data analysis employs an interactive data analysis model consisting of data reduction, data display, and conclusion/verification stages. The research findings indicate that eight types of translation techniques were applied, namely established equivalence, amplification, discursive creation, linguistic compression, compensation, linguistic amplification, adaptation, and modulation. The technique of established equivalence emerges as the most dominant translation technique applied. The translation methods tend to prioritize the source language by adopting communicative methods. The ideological stance adopted by the translator is domestication. Based on the application of these techniques, methods, and ideologies of translation, it can be concluded that the translator prioritizes audience comprehension in the target language.